2D Numerical Analysis of an H-Darrieus Hydrokinetic Turbine with Passive Improvement Mechanisms - GUEVARA MUÑOZ, Angie Judith; HINCAPIE ZULUAGA, Diego Andres; SIERRA DEL RÍO, Jorge Andres; COLMENARES QUINTERO, Ramon Fernando; TORRES LOPEZ, Edwar; RODRIGUEZ CABAL, Miguel Angel (Engineering Transactions, 2023)
H-Darrieus hydrokinetic turbines are an alternative for small hydroelectric plants. These turbines are considered to have a low environmental impact as they do not require reservoirs. However, they have limited self-starting capacity, which limits their use. Nevertheless, the configuration of passive mechanisms in the H-Darrieus turbines affects their performance, as they tend to increase the flow velocity. This study is part of a project with the aim to design and build a turbine to generate energy in the Colombian river scenario in non-interconnected zones. The objective of this study is to analyze the performance through numerical simulations of four H-Darrieus rotors to be configured with passive improvement mechanisms. The study was conducted using ANSYS® Fluent software, employing transient, two-dimensional models under constant operating conditions. Overlapping meshes were used for the stationary and rotating domain configuration. The results show that increased solidity leads to decreased tip speed ranges and increased maximum rotor power. Improvement in the self-starting capability was found with passive mechanisms employing a diffuser geometry. Among the tested configurations, the rotor configured with a Venturi-shaped mechanism achieved a remarkable 660% improvement in the power coefficient compared to configurations without such mechanisms.